PELAKSANAAN PENINDAKAN GANGGUAN KEAMANAN DAN KETERTIBAN DI LAPAS PEREMPUAN KELAS IIA JAKARTA (PERIODE 1 JANUARI 2023 S/D 31 DESEMBER 2023) - Sartika Wati, Eka; Zein Sgn, Subhan (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
Action is an effort to stop, reduce and localize security disturbances. This action is important to maintain security and order in correctional institutions and to provide sanctions appropriate to the actions committed by prisoners. In this research, we will discuss the arrangements for taking action against disturbances in security and order in the Class IIA women's prison in Jakarta and the obstacles to implementing action against disturbances in security and order in the Class IIA women's prison in Jakarta (period 1 January 2023 to 31 December 2023). In this research, we will discuss the legal research method used is a normative juridical legal research method supported by empirical data. Using a statutory approach and a conceptual approach. obtained from primary, secondary and tertiary legal material sources. Arrangements for the security and order of convicts in women's correctional institutions based on Article 64 Paragraph (3) Letter b of the Correctional Law Number 22 of 2022 concerning Corrections and Enforcement Rules are also contained in Article 38 in the Regulation of the Minister of Law and Human Rights Human Republic of Indonesia Number 8 of 2024 concerning the Implementation of Security and Order in Correctional Work Units which replaces the Regulation of the Minister of Law and Human Rights Number 6 of 2013 concerning Rules for Correctional Institutions and State Detention Centers. Obstacles in implementing action against disturbances in security and order in the Jakarta Class IIA Women's Prison (Period 1 January 2023 to 31 December 2023) include excess inmate capacity, lack of facilities and infrastructure, shortage of officers, not yet optimal intelligence systems, and external interference.